The Rosary and the Virgin Mary in Mexico: The Symbol of a Just War from 1883–1929 - Gómez-Rossi, Alfonso (The international journal of religion and spirituality in society, 2019)
During the last quarter of the nineteenth century and first thirty years of the twentieth, the Catholic laity was encouraged to pray and meditate on the mysteries of the Rosary to remedy perceived evils caused by the ideology of modernity, understood by devout Catholics as a threat to the well-being of humanity due to its attacks on the Catholic Church in Europe and the Western Hemisphere. Though the physical rosary is associated with the meditation on the events of Mary’s life and their connection to the earthly life of Christ, her son, Catholics also consider it a spiritual weapon to implore God’s intercession in worldly affairs, in favor of the mystical body of the Catholic Church. Beginning in 1883, when Leo XIII issued the first of a series of Encyclicals that encouraged Catholics to pray and meditate on the beads to 1929, when the Mexican movement of the Cristeros ended, the papacy asked its constituents to use the Rosary to defend the Church from the onslaught of the state in a series of civil movements that were vindicated as Just Wars against a secular state that acted as an enemy of its citizenry. Among Catholics who heeded the call were Mexicans, who used the Rosary to petition the Virgin and God to help them overthrow the Mexican government led by Plutarco Elías Calles.